Reflective functioning mediates the relationship between insecure adult attachment and the severity of prolonged grief symptoms - Serena Giunta; Giuseppe Mannino; Lucia Sideli; Maria C. Quattropani; Vittorio Lenzo (Health Psychology Research)
# Background